SARS-CoV-2 Infection Mimicking Neutropenic Fever during Chemotherapy for Acute Lymphoblastic Leukemia: A Case Report - Hyun Sik Kang (The Korean Society of Pediatric Hematology-Oncology, 2023)
Children with SARS-CoV-2 infection typically exhibit mild respiratory symptoms, with only a small proportion presenting with gastrointestinal symptoms. However, children and adolescents with cancer may develop severe illnesses when infected with respiratory viruses. Most patients are asymptomatic or have mild-to-moderate infections, but a significant percentage face severe or critical COVID-19-related illnesses. Diagnosing SARS-CoV-2 in pediatric patients is challenging because of frequent asymptomatic cases or those presenting with only a fever. In pediatric patients with SARS-CoV-2, heightened inflammatory markers and coagulation abnormalities are common. Increased levels of inflammatory markers and lymphopenia are risk factors for severe illness, making essential blood tests crucial as potential indicators of disease severity. Febrile neutropenia (FN), a common and potentially fatal side effect of chemotherapy, occurs in roughly 50% of children receiving cancer chemotherapy, and individuals with FN should remain vigilant for SARS-CoV-2 infection, even with mild symptoms. COVID-19-related fatalities occur in 4% of pediatric patients, which is significantly lower than the 25% observed in adult cancer patients but disproportionately higher than the 0.5% mortality rate among general pediatric cohorts. The case of a 12-year-old boy with neutropenic fever undergoing intensive anticancer therapy who was later confirmed to have SARS-CoV-2 infection highlights the importance of vigilance in such patients.